Pembagian Harta Waris dalam Tradisi Masyarakat Muslim di Gorontalo - Pongoliu, Hamid (Al-Manahij: Jurnal Kajian Hukum Islam, 2019)
Gorontalo has a customary principle derived from sharia law, and the sharia law is sourced from the Qur'an, hadith, ijmak and qiyas (adati-hula'a to syara'a, syara'a hula'a to Kitabi), which should reflect the existence of the implementation of the distribution of inheritance in Islam in the Gorontalo community. This customary principle can be a source of law if it is a rational act, not immorality, done always repeatedly, does not bring harm and does not conflict with the law of sharak. But in reality there is the implementation of inheritance that violates Islamic law, namely the distribution by way of deliberation, the determination of the amount of heirs equally, the delay in the distribution of inheritance, wills with houses given to girls, wills not to distribute inheritance, distribution of assets it depends on the will of the heir and the delay in the distribution of inheritance on the grounds that one of the parents is still alive. The distribution by deliberation and determination of the amount of the portion for each heir are equally acceptable as long as they follow the guidelines of the Compilation of Islamic Law article 183 and the concept of takharruj which was previously preceded by the Shari'a division. After the heirs know the size of the portion, then they may agree to share it in their own way or leave the inheritance according to Shari'a and agree to give to each other with other heirs.